Analytical Hierarchy Process Approach in Vendor Selection Strategy to Improve the Effectiveness of Goods and Services Procurement: Pendekatan Analytical Hierarchy Process Dalam Strategi Pemilihan Vendor Untuk Peningkatan Efektivitas Pengadaaan Barang dan Jasa - Calyca Didy Araminta; Joumil Aidil Saifuddin Z. S. (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
PT XYZ as a company engaged in the maritime services industry is committed to improving overall operational effectiveness. Effective procurement of goods and services is one of the keys to success in the smooth operation of PT XYZ. The challenge to the procurement process lies in making decisions by considering the advantages and disadvantages of vendors. Without the right method, vendor selection decisions can risk reducing service quality and increasing operational costs. Therefore, the application of Analytical Hierarchy Process plays an important role in optimizing vendor selection strategies. This method integrates inter-criteria and inter-alternative comparisons based on predetermined criteria. The four criteria used as consideration for vendor selection are Quality of Work, Plan Realization, Implementation Plan, and Implementation Response. From these criteria, an inter-alternative comparison of Vendor A, Vendor B, Vendor C, and Vendor D. The results of alternative priorities show that Vendor B is considered the most capable of increasing effectiveness in the process of procuring goods and services at PT XYZ with the highest priority weight of 0.3712 in SuperDecisions software, followed by Vendor A occupying the second priority, Vendor C occupying the third priority, and Vendor D occupying the last priority. Meanwhile, the highest to lowest priority criteria are Plan Realization, Quality of Work, Implementation Plan, and Implementation Response.